Study of Coherent $π^0$-Photoproduction on the Deuteron (Journal of Atomic and Molecular Sciences, 2011)
We consider the coherent $π^0$-photoproduction reaction on the deuteron, $γ d → π^0d,$ in the energy region from $π$-threshold up to 1 GeV using an enhanced elementary pion photoproduction amplitude on the free nucleon and a realistic high-precision $NN$ potential model for the deuteron wave function. Numerical results for total and differential cross sections are presented for which the sensitivity to various models for the elementary pion photoproduction operator is investigated. Considerable dependence of the results on the elementary amplitude is found at photon lab-energies close to $π$-threshold and above 600 MeV. In addition, the results for differential and total cross sections are compared with the available experimental data and a satisfactory agreement was found.